Physical States of Staphylococcal α-Toxin - Arbuthnott, John P. (1967)
At least three different forms of staphylococcal α-toxin have been shown to exist: soluble active α-toxin (α 3S), soluble inactive α-toxin (α(12s)), and insoluble inactive aggregate. Aggregation to the insoluble, biologically inactive form could be induced by brief heating to 60 C. The aggregate was dissociated by treatment with 8 m urea with reappearance of biological activity. Subsequent removal of urea by dialysis resulted in some spontaneous reaggregation to the insoluble state. The supernatant fluid obtained after dialysis contained soluble active α-toxin of high specific activity, possessing physical, toxic, and immunological properties closely resembling those of native toxin. The soluble biologically inert component (α(12s)) was identified as a third physical state. Negatively stained preparations of this material, when examined in the electron microscope, showed rings of approximately 100 A outside diameter containing 6 ± 1 subunits.